Erythroderma and Hypernatraemic Dehydration in Newborn - A Case report of Netherton Syndrome - Anneser, Verena; Mueller, Fabian; Wild, Florian; Metze, Dieter; Schneider, Holm; Steinhoff, Martin; Seeliger, Stephan (Klinische Pädiatrie, 2020)
Netherton syndrome (NS) is a rare, severe, autosomal recessive form of congenital ichthyosis, associated with a characteristic defect in the hair shaft (Trichorrhexis invaginata), erythroderma, and a pronounced atopic disposition due to an altered immune system. Its incidence is about 1:100,000 to 1: 200,000. The disease is caused by mutations in the gene SPINK5 (5q31-q32) which codes for the serine protease inhibitor LEKTI. Affected newborns show a non-uniform picture of generalized erythroderma with scaling of the skin and sometimes even present as Collodion babys. A serious complication during early infancy is hypernatremic dehydration resulting from the inadequate barrier function of the skin. The mucocutaneous barrier dysfunction also leads to recurrent infections, atopy, diarrhea, and intestinal malabsorption with concomitant failure to thrive.
CRIS-Team WoS Importer:2020-06-05